Fungi and their kingdoms - Lepp, Heino; Australia. Environment Australia; Australian Biological Resources Study (Canberra : Australian Biological Resources Study, 2002)
Poster featuring photographs of fungi by Heino Lepp, Peter McGee and Bruce Fuhrer. The logos of the Australian Biological Resources Study (ABRS) and Environment Australia appear lower left.
Caption title.
Part of the series Fungi of Australia.
Keywords: Fungi -- Australia -- Posters; Posters, Australian; Australia -- Posters; Australian